Sequence Analysis of APOE Gene Across Mammalian Species in Thailand - Bunyaluk, Dechawut; Srisanyong, Wilasinee; Amporn, Chalothon (Food Agricultural Sciences and Technology, 2021)
The current study utilized five mammalian species, including rhesus monkey (Macaca mulatta), Thai Bangkaew dog (Canis lupus familiaris), Thai domestic cat (Felis catus), tiger (Panthera tigris) and Thai domestic rabbit (Oryctolagus cuniculus) to survey the prevalence of apolipoprotein E isoform distribution. Screening for the three common apolipoprotein E (APOE) isoforms (E2, E3 and E4) was achieved using APOE gene sequencing analysis. The results clearly revealed the homology of APOE protein sequences in analyzed mammals, ranging from 59.74 96.22% and 64.15-100% identity and similarity, respectively. Thai Bangkaew dog, Thai domestic cat, tiger, and rhesus monkey show arginine at the positions 112 and 158, which are found in APOE4 of human. This result demonstrates that for these five investigated mammals are apolipoprotein E4, and is associated with an increased genetic risk factor of both Alzheimer’s disease (AD) and coronary heart disease (CHD). Remarkably, Thai domestic rabbit has cysteine at position 112 and arginine at position 158. This indicates that the APOE isoform of Thai domestic rabbit is identical to that of human APOE3, and is not associated with the risk for Alzheimer’s disease. The evolutionary history inferred that Thai Bangkaew dog, Thai domestic cat and tiger are distinguishable as a group from Thai domestic rabbit, rhesus monkey and human by certain differences in amino acid sequences. This study provides valuable genetic resources for future study to identify potential biomarkers of neurodegenerative diseases in mammals using apolipoprotein E gene expression profiles.